High-flux high-energy ion beam production from stable collisionless shock acceleration by intense petawatt-picosecond laser pulses. (28th March 2019) - He, H; Qiao, B; Shen, X F; Yao, W P; Xie, Y; Zhou, C T; He, X T; Zhu, S P; Pei, W B; Fu, S Z
Abstract: A scheme to achieve stable collisionless shock acceleration (CSA) of ions from a near-critical plasma by intense petawatt-picosecond laser pulses is proposed, where the plasma is confined in a high-Z solid tube. The application of the tube, on the one hand, restrains the plasma from transverse thermal expansion, helping to sustain sufficient density steepening required for shock formation and maintenance; on the other hand, due to the induced sheath field along its wall, pinches hot electrons for recirculation near laser axis, aiding to reach efficient plasma heating that is crucial to have a strong shock velocity for ion reflection. Consequently, stable ion CSA can be maintained for picosecond time scales, resulting in production of high-flux high-energy ion beams. Two-dimensional PIC simulations show that proton beams with narrow energy spread between 50 and 80 MeV and high flux with particle number about 10 12 are produced by a laser pulse at intensity 8.8 × 10 19 W cm −2 and duration 1 ps. By extending the pulse duration to 3 ps, over 100 MeV high-flux proton beams are obtained.